Cambio de época: Los imperios tiemblan y contraatacan - Cockcrofr, James D. (2024)
There Is a global decline of the imperialisms and historical changes in the correlation of social forces, of class and of nations. There have emerged new popular movements leaded by "those down below", who include to the ancestor people, the peasantry, the unemployed, the people who do precious work (flexible or unstable), and the majority of intermediate classes. There is a decline of North American power and a revolutionary worldwide wave. The indo - African- Latín America experiments multiple changes and the emergency of new organisms like CELAC, South Bank, South Monetary Found, the Bank of ALBA; South American Security Council (twelve- nation military ring, which exclude to the United States); UNASUR amount others. The empires fight back. The US reinforces their military power around the world and in Latin America. However, these nations resist with an increasing force. Nevertheless, we must be realistic. Everybody knows the, with partial exception of Cuba- we live in capitalist economies, and that the governments of the south depend too much on the fossil fuel exportations. We know that neoliberalism continues in States, which supposedly are post neoliberals. ln addition, there are a lot of interna! problems of the reformist and revolutionary processes of our America and in our own social movements. At the same time, there are serious tensions movements and the progressive States that we should turn into creative tensions - like Jose Marti said "with everybody and for everybody's welfare".